Down-regulation of Long Noncoding RNA MALAT1 Protects Hippocampal Neurons Against Excessive Autophagy and Apoptosis via the PI3K/Akt Signaling Pathway in Rats with Epilepsy - Wu, Qiang; Yi, Xuewei (Journal of molecular neuroscience, 2018)
Epilepsy is a common chronic brain disorder and is characterized by an enduring predisposition to generate seizures. The hippocampus is especially vulnerable to seizure-induced damage. In this study, we explore the ability of long noncoding RNA (lncRNA) metastasis-associated lung adenocarcinoma transcript 1 (MALAT1) to influence the autophagy and apoptosis of hippocampal neurons in epilepsy and the underlying mechanism involving the PI3K/Akt signaling pathway. Seventy-two Sprague-Dawley rats were assigned to normal, sham, Ep, Ep + si-NC, Ep + si-MALAT1, and Ep + si-MALAT1 + LY groups. Fluorescence in situ hybridization kit was employed to determine the MALAT1 in the brain tissues. Reverse transcription quantitative polymerase chain reaction (RT-qPCR) and western blotting were performed to determine the expression of MALAT1, mRNAs, and proteins. The autophagy of hippocampal neurons was evaluated under a transmission electron microscope and their apoptosis was evaluated using TUNEL staining. We found that MALAT1 and c-Met were enriched while microRNA-101 (miR-101) decreased in rats with epilepsy. The demonstration showed that MALAT1 binds to miR-101, thus regulating c-Met. In rats with epilepsy, MALAT1 depletion mediated by anti-MALAT1 siRNA resulted in activation of PI3K/Akt signaling pathway and loss of hippocampal neurons. LY294002, an inhibitor of PI3K/Akt signaling pathway, could reverse the events caused by MALAT1 knockdown. Taken together, these findings indicate that down-regulation of MALAT1 activates the PI3K/Akt signaling pathway to protect hippocampal neurons against autophagy and apoptosis in rats with epilepsy.